Awareness Levels of School Teachers Regarding Healthy Vision And Eye Screening In Dist Gautam Budh Nagar, U.P. - Agrawal, Deepika; Tyagi, Neha; Nagesh, Seetha Ramaiah (National Journal of Community Medicine, 2018)
Background: School teachers in government schools are contribut- ing in eye screening of students through school health services. The private schools also need to contribute more in these services by raising the knowledge regarding vision, healthy practices for healthy eyes and vision as well as screening of the eyes for refrac- tive errors. The study aims to find the knowledge levels of private school teachers regarding healthy vision practices and eye screen- ing, train the teachers in eye screening and assess the level of im- provement in their knowledge after the training. Methods: 14 schools in the field practice areas of the department of Community Medicine were enrolled for the study. Two teachers from each school were randomly selected for training and assess- ment. Pre and post assessments were made on the teachers during the training workshop. The data thus collected was analysed using SPSS 20. Results: None of the schools had implemented the School Health Program. Knowledge among teachers was found to be poor in many aspects of eye and vision health which showed a remarkable improvement after the training (P values ranging from .003-.02). Conclusion: Private school teachers should be trained for eye screening and utilized for early identification of uncorrected re- fractive errors in children.